2010 Annual International Conference of the IEEE Engineering in Medicine and Biology 2010
DOI: 10.1109/iembs.2010.5626627
|View full text |Cite
|
Sign up to set email alerts
|

Is pulse transit time a good indicator of blood pressure changes during short physical exercise in a young population?

Abstract: The Pulse Transit Time (PTT) is generally assumed to be a good surrogate measure to comfortably track blood pressure (BP) and blood pressure changes. This paper investigates PTT variations for healthy young subjects during a sequence of short-term physical exercises. PTT was measured by two different methodologies having different measurement accuracies as well as underlying assumptions: the total PTT from heart to fingertip and the difference of fingertip and earlobe PTTs. Small non consistent changes and ver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
51
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(53 citation statements)
references
References 11 publications
1
51
0
1
Order By: Relevance
“…Proença et al estimated SBP with this mathematical model Equation (6) using both PTT and PAT [82]. They determined PTT from two PPG sensors placed at the earlobe and at a finger, and PAT with PEP adjustment using the impedance cardiogram.…”
Section: Logarithmic Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Proença et al estimated SBP with this mathematical model Equation (6) using both PTT and PAT [82]. They determined PTT from two PPG sensors placed at the earlobe and at a finger, and PAT with PEP adjustment using the impedance cardiogram.…”
Section: Logarithmic Modelmentioning
confidence: 99%
“…Here, a and b are subject-specific constants and they can be obtained through a regression analysis between the reference BP and the corresponding "Time Delay" [82]. Proença et al estimated SBP with this mathematical model Equation (6) using both PTT and PAT [82].…”
Section: Logarithmic Modelmentioning
confidence: 99%
“…Although many studies have previously shown that PTT is capable of predicting changes in BP and vascular tone over a short period of time, its reliability as a marker for cardiovascular risks, its inverse relation to beat-to-beat blood pressure, and the accuracy of the methods used to calculate PTT are often questioned and are still being investigated [8], [9]. Also, the relative changes in PTTs measured from multiple sites simultaneously in response to a raise in BP has not been investigated previously.…”
Section: Introductionmentioning
confidence: 99%
“…The ICG target proximal point is the ICG-B point, which indicates the opening of the aortic valve. The ICG-B point is however difficult to locate in individual cycles in ICG signals recorded during activity [21]. In this work, we have chosen an approach were the B-point is estimated based on the time gap (in ms) between the ECG-R wave and the ICG-C peak (the maxima on the ICG curve), TRC.…”
Section: B Calculation Of Pulse Transit Timementioning
confidence: 99%
“…We have considered an averaged PPT value, and, assuming the error in B detection had a random component, we found that the averaging decreased the error. A change in mean blood pressure of 10 mmHg is expected to give a change in PTT of about 8ms-16ms [21]. Their calculations were based on PTT values in the range 100ms to 200ms.…”
Section: B Calculation Of Pulse Transit Timementioning
confidence: 99%